Panels of protein biomarkers and non-protein markers in the diagnosis of the ovarian cancer - Denel, Marta; Marczak, Agnieszka (Menopause Review/Przegląd Menopauzalny, 2013)
Ovarian cancer is, not without reason, called the “silent killer”. It is one of the most difficult problems in gynecologic oncology. In the absence of specific symptoms it is recognized in the advanced stages of the disease, which greatly reduces the effectiveness of therapy. Therefore, there is a need for new methods for early diagnosis of cancer. They can not only assist in the detection of cancer but also provide information on the effectiveness of the treatment. It is important that the tumour markers are determined in the least invasive and less expensive way so as to be used for large-scale screening. The current standard is to use a protein marker CA125, which is not sufficiently sensitive and specific. So it is supported by determination of additional protein markers and statistical methods. It is reasonable to use the so-called biomarker panels, the test of more than one marker to achieve the highest sensitivity and specificity. The algorithm ROMA and test OVA1 are used. Currently, studies on the introduction of further markers, including non-protein markers are underway. With the rapid development of genetics, proteomics and metabolomics, a number of compounds are identified which can be used in screening tests for the early detection of ovarian cancer. This paper presents the latest news on biomarkers in the diagnosis and treatment of ovarian cancer. The analysis of genetic material, including both the detection of gene mutations and epigenetic changes and microRNA studies, seems to be very promising.